Kinetics, cross‐reactivity, and specificity of Bet v 1‐specific IgG4 antibodies induced by immunotherapy with birch pollen. Issue 11 (21st September 2013) - Subbarayal, B.; Schiller, D.; Möbs, C.; de Jong, N. W.; Ebner, C.; Reider, N.; Bartel, D.; Lidholm, J.; Pfützner, W.; Gerth van Wijk, R.; Vieths, S.; Bohle, B.
Abstract: Background: IgE antibodies specific for the major birch pollen allergen frequently cross‐react with Bet v 1 homologous food proteins, for example Cor a 1 in hazelnut and Mal d 1 in apple. Specific immunotherapy with birch pollen (BP‐SIT) induces IgG4 antibodies that inhibit IgE binding to Bet v 1. However, information on cross‐reactivity of BP‐SIT‐induced Bet v 1‐specific IgG4 antibodies with food allergens is limited. In this study, we investigated the kinetics of production, cross‐reactivity, and IgE‐blocking activity of Bet v 1‐specific IgG4 antibodies emerging during conventional BP‐SIT and whether IgG4‐epitopes overlapped with IgE epitopes. Methods: IgE and IgG4 levels specific for Bet v 1, Mal d 1, and Cor a 1 were determined in 42 birch pollen–allergic patients before and during BP‐SIT. Inhibition of IgE binding was studied by IgE‐facilitated antigen‐binding assays and basophil activation tests. Furthermore, inhibition of IgE‐mediated activation of food allergen‐reactive Bet v 1‐specific T‐cell lines was assessed. Competitive immunoscreening of phage‐displayed peptides was applied to select mimotopes recognized by IgE and IgG4 antibodies, respectively. The resulting mimotopes were mapped on the surface of the 3D structure of the allergens using a computer‐based algorithm. Results: BP‐SIT significantly increased Bet v 1‐ and food allergen‐reactive IgG4 antibodies. In parallel, allergen‐specific IgE levels decreased significantly. Sera containing food allergen‐reactive IgG4 antibodies inhibited IgE binding, basophil activation, and IgE‐mediated food allergen‐induced T‐cell proliferation. Predicted IgE and IgG4 epitopes on all allergens showed high overlap. Conclusion: Our results indicate that BP‐SIT may induce Bet v 1‐specific IgG4 antibodies that cross‐react with related food allergens and inhibit IgE binding by epitope competition.